Formation of protein oleogels via capillary attraction of engineered protein particles. (December 2022) - Wang, Gao-Shang; Chen, Hong-Yu; Wang, Li-Juan; Zou, Yuan; Wan, Zhi-Li; Yang, Xiao-Quan
Abstract: Edible oleogels have gained popularity as an approach for formulating food products, profiting from improving nutritional profiles related to health-related concerns, and playing an essential role in food processing. Protein oleogels provide an additional opportunity to load and deliver a high proportion of natural macronutrient in lipid-based food products. However, structuring oleogels with proteins directly were rarely reported, which has greatly limited their practical applications. Herein, we proposed a simple and robust method for structuring protein oleogels. By taking advantage of the improved interparticle cohesion through adding a much small amount of water (e.g., 2%) dispersed by ball milling, a space-spanning fractal network of engineered colloidal protein nanoparticles was formed, allowing for physically trapping the liquid oil into a self-standing gel-like system. Rheology and confocal laser microscopy imaging were adopted to investigate the viscoelasticity and microstructure of the resulting oleogels, showing that these capillary protein oleogels can be designed and fabricated with tunable properties upon water addition. Meanwhile, protein oleogels can be successfully formed by this approach, varying from proteins with different wettability, as well as oils differing in polarity. Overall, our findings raise the possibility of structuring protein oleogels with high operability and easy scale-up in practical applications. Graphical abstract: Capillary suspension promises a new approach for structuring protein oleogels. Image 1 Highlights: Protein oleogels were successfully prepared through adding a small amount of water into protein oily suspension by ball milling. A morphological transformation of zein protein oleogels from a pendular network to a funicular state, finally to a compact capillary aggregate network occurs. These capillary-induced protein oleogels mainly depend on the composition, particle characteristics, and processing conditions. Capillary-induced protein oleogels can be successfully fabricated varying from proteins, as well as oils.